2010
DOI: 10.1212/wnl.0b013e3181e8e6d0
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of posttraumatic epilepsy 35 years following combat brain injury

Abstract: Background:The Vietnam Head Injury Study (VHIS) is a prospective, longitudinal follow-up of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
118
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(126 citation statements)
references
References 35 publications
6
118
0
2
Order By: Relevance
“…One implication of these findings is that the rate of ictal activation might be useful as a gauge of seizure probability. Severity of brain injury correlates with the incidence and severity of the subsequent epilepsy (Ferguson et al, 2010;Raymont et al, 2010). The current data support the idea that these correlations may arise from loss of afferent and efferent connections and the consequent degree of recurrent connectivity in the epileptic focus.…”
Section: Clinical Implications Activation Of Epileptic Networksupporting
confidence: 78%
See 1 more Smart Citation
“…One implication of these findings is that the rate of ictal activation might be useful as a gauge of seizure probability. Severity of brain injury correlates with the incidence and severity of the subsequent epilepsy (Ferguson et al, 2010;Raymont et al, 2010). The current data support the idea that these correlations may arise from loss of afferent and efferent connections and the consequent degree of recurrent connectivity in the epileptic focus.…”
Section: Clinical Implications Activation Of Epileptic Networksupporting
confidence: 78%
“…Post-traumatic epilepsy is increasingly being recognized as an important public health problem (Ferguson et al, 2010;Raymont et al, 2010). We know very little about the processes that underlie the development of epilepsy after brain injury (Lowenstein, 2009;Noebels et al, 2012;Pitkänen and Immonen, 2014), and thus cannot develop rational treatments for this particularly refractory form of secondary epilepsy (Temkin, 2009;Prince et al, 2012;Goldberg and Coulter, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Gorin wrote on a few postictal symptoms in PTE, of which we found 11% of these symptoms in our results [14]. We found that the time from brain injury to PTE for the majority of patients (51%) was 1 year, which was similar to the value published by Frey (86%, 2 years) and Raymond (57.6%, 1 year) [5,15].…”
Section: Discussionsupporting
confidence: 89%
“…Veterans are at a higher risk of developing seizures than the general public, in part due to the increased rate of traumatic brain injuries (TBIs) experienced during combat and while in service [1][2][3][4][5]. In response to concerns of increased posttraumatic epilepsy among returning servicemembers from current conflicts, the U.S. Congress passed the Veterans' Mental Health and Other Care Improvements Act of 2008, mandating the establishment of the Veterans Health Administration (VHA) Epilepsy Centers of Excellence (ECoE).…”
Section: Introductionmentioning
confidence: 99%